2017
DOI: 10.1111/ijsw.12268
|View full text |Cite
|
Sign up to set email alerts
|

Child protection in China: Changing policies and reactions from the field of social work

Abstract: This article offers a general review of the development of national policies on child protection in China. It offers an in‐depth analysis of related legislation enacted between 2010 and 2015 that have had an impact on child protection and related historical, cultural and legal issues. Furthermore, in the study we examined the emerging role of social work in preventing and responding to child abuse and neglect in China. Major findings of the research include: (i) policies concerning child protection have been h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…We identified relevant published and unpublished literature, including articles, chapters, books, policy documents, and laws, through the search strategies detailed above. We analyzed this literature through a country‐specific lens, as articulated by Zhao, Hämäläinen, and Chen (). Specifically, we focused on policy development in the USA and China, in the area of child welfare.…”
Section: Methodsmentioning
confidence: 99%
“…We identified relevant published and unpublished literature, including articles, chapters, books, policy documents, and laws, through the search strategies detailed above. We analyzed this literature through a country‐specific lens, as articulated by Zhao, Hämäläinen, and Chen (). Specifically, we focused on policy development in the USA and China, in the area of child welfare.…”
Section: Methodsmentioning
confidence: 99%
“…Despite its rapid development, China is still deeply influenced by Confucianism and patriarchal culture, under which the child is the personal property of the parent rather than an independent individual, and child obedience to parents is regarded as important to the maintenance of family order (Peng et al, 2015). Chinese people generally regard physical punishment as a necessary parenting technique (Zhao et al, 2017). A multi-country comparison found that Chinese people have the highest threshold for labeling behaviors as maltreatment (Mesman et al, 2020).…”
Section: Ethnic Disparities In Maltreatment Traumamentioning
confidence: 99%
“…The idea of reporting child abuse advocated by the new Act is still contrary to culturally-justified tolerance toward corporal punishment and the belief that child discipline is a family matter, which is illustrated in our study. It is likely to be a long time before such a reporting mechanism is widely accepted (Zhao, Hamalainen, & Chen, 2017).…”
Section: Implications For Policymentioning
confidence: 99%